2021
DOI: 10.6007/ijarped/v10-i2/9790
|View full text |Cite
|
Sign up to set email alerts
|

Parents as Multidimensional Reading Partners for Young Children’s Reading Development: A Scoping Review

Abstract: This scoping review aims to identify the appropriate roles of parents that can help address problems related reading development amongst young learners. The topic of parents as reading partners needs to be explored given that having the involvement of parents would advantage language learners to minimize their reading problems from different aspects including interest, fluency and comprehension in reading. Parents' role is in fact, an effective indicator of high language proficiency level. Numerous studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…In Hong Kong, Lau and Richards (2021) investigated how children's exposure to a literate home environment affected their language and reading development and the findings showed that students' letter knowledge, phonemic awareness, vocabulary, and word comprehension improved significantly when they were actively supported by their families. In Malaysia, Wong and Tan (2021) looked at how parents might help their children in many different ways as they read. The scope-reviewed method was used for this investigation.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%
“…In Hong Kong, Lau and Richards (2021) investigated how children's exposure to a literate home environment affected their language and reading development and the findings showed that students' letter knowledge, phonemic awareness, vocabulary, and word comprehension improved significantly when they were actively supported by their families. In Malaysia, Wong and Tan (2021) looked at how parents might help their children in many different ways as they read. The scope-reviewed method was used for this investigation.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%